2017
DOI: 10.1007/s00223-017-0336-6
|View full text |Cite
|
Sign up to set email alerts
|

Osteomicrobiology: A New Cross-Disciplinary Research Field

Abstract: The mutualistic interaction between the gut microbiota (GM) and its host profoundly shapes many aspects of our physiology. The composition and activity of the gut microbiota is modulated by environmental factors such as dietary habits and antibiotic treatments. In rodents, studies demonstrate that the GM is a crucial regulator of bone metabolism and that modulation of the GM composition by probiotic interventions can prevent castration-induced bone loss. Short-term colonization of germ-free mice with GM result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 42 publications
3
38
0
Order By: Relevance
“…Commensal gut microbiota effects on the skeleton have commonly been proposed to occur through a direct gut–bone axis . Our prior work revealed that the commensal gut microbiota profoundly stimulates innate and adaptive immunity in the liver, which led us to postulate that gut microbiota effects on the skeleton are mediated, in part, by a gut–liver–bone axis .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Commensal gut microbiota effects on the skeleton have commonly been proposed to occur through a direct gut–bone axis . Our prior work revealed that the commensal gut microbiota profoundly stimulates innate and adaptive immunity in the liver, which led us to postulate that gut microbiota effects on the skeleton are mediated, in part, by a gut–liver–bone axis .…”
Section: Introductionmentioning
confidence: 98%
“…(39)(40)(41)(42) Commensal gut microbiota effects on the skeleton have commonly been proposed to occur through a direct gut-bone axis. (43,44) Our prior work revealed that the commensal gut microbiota profoundly stimulates innate and adaptive immunity in the liver, which led us to postulate that gut microbiota effects on the skeleton are mediated, in part, by a gut-liver-bone axis. (13) The current report reveals that SFB has pro-osteoclastic/antiosteoblastic actions impairing postpubertal skeletal development, which appear to be mediated through immunomodulatory effects in both the gut and liver.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, subsets of immune cells, various differentiation stages of bone cells (Ducy, Schinke, & Karsenty, ; Teitelbaum, ), and different modes of local and systemic cell activation generate a complex picture of this research area. Osteoimmunology was recently open to a new field which considers the impact of the microbiome on bone homeostasis in health and disease—osteomicrobiology (Ohlsson & Sjogren, ). For example, short‐chain fatty acids, the main metabolites derived from microbial fermentation of dietary fibres, can regulate osteoclast metabolism and bone homeostasis (Lucas et al., ).…”
Section: Preamblementioning
confidence: 99%
“…Osteomicrobiology, based on the mutual interaction of not only the gut microbiota but also the microbiome of the oral cavity with the host, is a new term and an emerging research field that bridges the gap between the microbiome and osteoimmunology (Hsu & Pacifici, ; Ohlsson & Sjogren, ). Consistent observations are based on periodontitis models treated with probiotics.…”
Section: Preamblementioning
confidence: 99%
“…By modulating the immune system, GM is becoming a new player in the regulators of bone turnover and function. Considering the interplay between bone physiology, gastrointestinal tract content, microbiology, and immunology, Ohlsson and Sjögren are proposing the term "Osteomicrobiology" to cover this field where GM changes are capable of preventing ovariectomy-induced bone loss [12]. Such a cross-talk appears to exist between GM and skeletal muscle too.…”
mentioning
confidence: 99%